2018
DOI: 10.1021/acs.iecr.7b05217
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effect on the Rheological Behavior of Waxy Crude Oil with Comb-Type Copolymers Bearing Azobenzene Pendant

Abstract: In this work, a pressure responsive poly­(α-octadecene-co-maleic acid azobenzene amide) (Azo-MAC) was synthesized and able to enhance the flowability of waxy crude oil with asphaltenes significantly under high pressure. High-pressure UV–vis spectrometer was used to characterize its pressure response under pressures. The onset temperature and enthalpy during wax crystallization of Liaohe waxy crude oil under various pressures were determined by using high-pressure differential scanning calorimeter. The viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The SP and CFPP of diesel untreated with PPDs are −7 and −2 °C, respectively. In our previous work, the effects of chain length of PPDs were discussed because at the length of near 17.1, the PPD presents a better depression. ,, Thus, the R 1 MC-MB-NVP (R 1 = C 14 and C 16 ) were prepared and used as PPDs in this study. The effect of R 1 MC-MB-NVP (R 1 = C 14 and C 16 ) on the SP and CFPP of diesel fuel is presented in Tables and .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SP and CFPP of diesel untreated with PPDs are −7 and −2 °C, respectively. In our previous work, the effects of chain length of PPDs were discussed because at the length of near 17.1, the PPD presents a better depression. ,, Thus, the R 1 MC-MB-NVP (R 1 = C 14 and C 16 ) were prepared and used as PPDs in this study. The effect of R 1 MC-MB-NVP (R 1 = C 14 and C 16 ) on the SP and CFPP of diesel fuel is presented in Tables and .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Many studies have indicated that the main substances used as PPDs include the ethylene and vinyl acetate copolymers (EVA), , ethylene and butene copolymers (PE–PEB), , copolymers of maleic anhydride (MA), and copolymers of alpha olefins , and their derivatives. It is well-known that PPDs have appropriate lengths of alkyl side chain and polar groups, which can effectively improve the cold flow properties of diesel fuel. Thus, the molecular structure of PPDs is designed on the basis of the polarity-matching principle and carbon chain-matching principle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in related work, a high-pressure capillary rheometer for the study of reservoir fluids was developed and the transition from Newtonian to non-Newtonian behavior observed at elevated pressures for some heavy oils . On the modeling side, Li et al , proposed an exponential–law relationship between viscosity and pressure. These last authors furthermore suggested that, at elevated pressure, the conformation transformation from cis to trans of azobenzene groups may destroy the assembly of asphaltenes, disturb the crystallization of paraffins and thus improve the flowability of oils.…”
Section: Introductionmentioning
confidence: 99%
“…Among various viscosity reduction practices, chemical additives serve as a promising solution because of their stable performance and cost efficiency. For example, researchers have widely used amphipathic polymers, such as α-olefins–maleic anhydride copolymers, ethylene–vinyl acetate copolymers, and poly­[ N , N -(dimethylamino) ethyl methacrylate] (PDMA)-poly­(lauryl methacrylate) (PLMA) copolymers, to stabilize crude oil in water by forming emulsions, and the effect of internal and external parameters such as chain lengths, hydrophilicity/hydrophobicity balance, as well as pH and ionic strength on the emulsification process, has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%